PENERAPAN INTERNATIONAL SHIP AND PORT FACILITY SECURITY CODEGUNA MENJAMIN KEAMANAN DI KM. MENTARI SUCCESS (PPPM - POLITEKNIK PELAYARAN SURABAYA, 2022)
Application of ISPS Code in KM. MENTARI SUCCESS to prevent vessel security threats at harbors is still a lot of drawbacks due to the lack of crew knowledge about the importance of ISPS Code this can be seen when the watchkeeping at the unloading port when berthing and when anchored in the anchor area. crews who do not know the official procedures keep in line with the ISPS Code are finded and this case must be have solve as soon as possible to achieve a safe and conducive ship environments. The ISPS Code is a provision and procedure to prevent acts of terrorism threatening the security of passengers, crew and ships. The neglect and lack of knowledge of the crew on duty may put the security of the vessel in jeopardy. Therefore, the required knowledge and discipline of the crew is trained and guaranteed in maintaining security on board, in accordance with the ISPS Code security system. The method of this minithesis used Qualitative Descriptive. In this case the authors make direct observations when practicing the sea above KM.MENTARI SUCCESS. The results obtained from this study that the provision of training and training, and gift and punishment. From the results of the evaluation of the two alternative solutions problem, it was found that each alternative has advantages and constraints that will be faced in its application on board. However, from both alternatives, with reference to the percentage consideration of the constraints faced, the best alternative solution is found to be the most appropriate solution to solve. Keywords : ISPS Code, Security Patrol, Watchkeeping